Symmetry breakings and topological solitons in mercury based d-wave superconductors - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
This study is devoted to examine high temperature superconductors by the concept of symmetry breakings. The global gauge symmetry is broken at Meissner transition temperature, T-c, in high temperature cl-wave superconductors. In addition to this symmetry breaking, the time reversal symmetry breaking phenomenon becomes observable on paramagnetic Meissner effect at paramagnetic Meissner effect temperature, T-PME. Furthermore, the concept of symmetry breakings has been discussed by the phenomenon of critical quantum chaos in the mercury cuprates which is one of the best examples to understand the chaotic transitions. From this point of view, T-c and T-PME have been suggested as chaotic transition points. Moreover, T-PME is predicted as the breaking point of electroweak symmetry as well. Furthermore, we have also proposed that the double helix quantum wave occurs in the quantum primitive cell of cuprates due to the breaking of the room temperature symmetry of the system at T-c. When time period of the wave is taken infinite, the double helix quantum wave can be considered as a topological soliton of the coherent system. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: HIGH-T-C; TIME-REVERSAL SYMMETRY; GAUGE-INVARIANCE; TEMPERATURE; STATE; SUSCEPTIBILITY; PARTICLES; PHASE